Models of Change in Canada’s Refugee Status Determination Process - Jackman, Barbara (Refuge: Canada’s Journal on Refugees, 1984)
It is not possible here to outline all cri- ticisms of the refugee-status determina- tion process. Many of these criticisms are directed at secondary issues arising from the actual practices followed by the Immigration Commission - prob- lems with work authorizations, wel- fare, settlement assistance and other such matters. Rather, I will attemptonly to outline the primary concerns with the present process and to put into context the proposals for change.